Respuesta :
A) h(x)+g(x)=(3x-4)+(9x+1)=12x-3
B) g(x) + f(x)=(9x+1)+(7x+2)=16x+3
C) g(x)*h(x)= (9x+1)(3x-4)=27x²+3x-36x-4=27x²-33x-4
D)h(x)-g(x)=(3x-4)-(9x+1)= - 6x -5
if f(x)= -7x +2
B) g(x)+f(x)=(9x+1)+(-7x+2)=9x-7x+1+2=2x+3
answer B
B) g(x) + f(x)=(9x+1)+(7x+2)=16x+3
C) g(x)*h(x)= (9x+1)(3x-4)=27x²+3x-36x-4=27x²-33x-4
D)h(x)-g(x)=(3x-4)-(9x+1)= - 6x -5
if f(x)= -7x +2
B) g(x)+f(x)=(9x+1)+(-7x+2)=9x-7x+1+2=2x+3
answer B
The only option that is equivalent to 2x + 3 is;
Option B; g(x) + f(x)
We are given;
h(x) = (3x - 4)
f(x) = (-7x + 2) (The correct one has negative sign before the 7)
g(x) = (9x + 1)
Option A; h(x) + g(x)
Plugging in the relevant equations gives;
(3x - 4) + (9x + 1)
⇒ 3x - 4 + 9x + 1
⇒ 12x - 3
Option B; g(x) + f(x)
Plugging in the relevant equations gives;
(9x + 1) + (-7x + 2)
⇒ 9x + 1 - 7x + 2
⇒ 2x + 3
Option C; g(x) * h(x)
Plugging in the relevant equations gives;
(9x + 1) × (3x - 4)
⇒ 27x² + 3x - 36x - 4
⇒ 27x² - 33x - 4
Option D: h(x) - g(x)
Plugging in the relevant equations gives;
(3x - 4) - (9x + 1)
⇒ -6x - 5
The only option that corresponds to 2x + 3 is Option B.
Read more at; https://brainly.com/question/9592040